Continuity of care and mortality in people with schizophrenia. Issue 4 (9th July 2021) - Macdonald, Alastair; Adamis, Dimitrios; Broadbent, Matthew; Craig, Tom; Stewart, Rob; Murray, Robin M.
Abstract : Background: People with schizophrenia have shortened lives. This excess mortality seems to be related to physical health conditions that may be amenable to better primary and secondary prevention. Better continuity of care may enhance such interventions as well as help prevent death by self-injury. Aims: We set out to examine the relationship between the continuity of care of patients with schizophrenia, their mortality and cause of death. Method: Pseudoanonymised community data from 5551 people with schizophrenia presenting over 11 years were examined for changes in continuity of care using the numbers of community teams caring for them and the Modified Modified Continuity Index. These and demographic variables were related to death certifications of physical illness from the Office of National Statistics and mortal self-injury from clinical data. Data were analysed using generalised estimating equations. Results: We found no independent relationship between levels of continuity of care and overall mortality. However, lower levels of relationship continuity were significantly and independently related to death by self-injury. Conclusions: We found no evidence that continuity of care is important in the prevention of physical causes of death in schizophrenia. However, there is evidence that declining relationship continuity of care has an independent effect on deaths as a result of self-injury. We suggest that there should be more attention focused on the improvement of continuity of care for these patients.